PARTICIPATION IN CHRONIC DISEASE PREVENTION PROGRAMS AMONG OLDER ADULTS LIVING IN RURAL AND URBAN SETTINGS. (11th November 2018) - Schwingel, A; Jansen, T; Bobitt, J; Payne, L
Abstract: This study aims to examine factors influencing completion of Chronic Disease Self-Management Program (CDSMP) and Diabetes Self-Management Program (DSMP) between rural and urban populations. Programs were implemented throughout 102 sites across the state of Illinois. Addresses were then geocoded using Google Earth Pro, distance travelled by each participant to their workshop site was calculated using the Origin-Destination Cost Matrix ArcGIS Network Analyst tool. Census Bureau's county classifications of Urban/Rural was adopted. The overall sample included 1, 003 older adults, average age 71.2 years. Of these, 941 participants lived in urban counties and 62 in rural counties in Illinois. A total of 757 participants completed 4 or more sessions of the program (4.2 sessions). Identifying as "Black or African-American", and more time spent in physical activity were positively correlated to program completion in urban settings. Also, there was a negative correlation between self-reported number of days per month participants felt physically not good, and self-reported number of days participants felt limited to carry out daily activities. Neither of these associations were significant for the rural sample. In rural settings, there was a negatively significant correlation between miles traveled and program completion. Findings from this study underscore differences in factors associated with completion of chronic disease programs among rural and urban older adults. To promote completion among participants in urban settings, strategies should focus on less physically active individuals and increase cultural competence. To increase participation in rural settings, workshops need to be more accessible to cut down on travel time.